Why High-Intensity NPPV is Favourable to Low-Intensity NPPV: Clinical and Physiological Reasons. (4th July 2017) - Schwarz, S. B.; Magnet, F. S.; Windisch, W.
ABSTRACT: High-intensity non-invasive positive pressure ventilation (NPPV) was originally described for chronic hypercapnic chronic obstructive pulmonary disease (COPD) patients in 2009, and refers to a specific ventilatory approach whereby NPPV settings are aimed at achieving the lowest arterial partial pressure of carbon dioxide (PaCO2 ) values possible. Thus, high-intensity NPPV requires ventilator settings to be increased in a stepwise approach to either an individually tolerated maximum, or to the levels necessary to achieve normocapnia. This differs from the classic approach to low-intensity NPPV, which comprises considerably lower ventilator settings and typically fails to lower elevated PaCO2 values. The ongoing discussion about whether or not long-term NPPV should be used in chronic hypercapnic COPD patients is based on the observation that many studies in the last two decades have failed to provide evidence for this particular patient cohort. In addition, these trials preferably used low-intensity NPPV. There is now, however, increasing evidence to suggest that high-intensity NPPV is capable of improving important physiological parameters such as blood gases and lung function, as well as health-related quality of life. Moreover, this approach also produced positive outcomes following two recent randomized controlled trials, e.g., improved survival rates in stable COPD patients, and admission-free survival in patients with persisting hypercapnia following acute in-hospital NPPV to treat acute acidotic respiratory failure. As a consequence, the time has now come to evaluate the impact of long-term NPPV on both the physiological and clinical outcomes, with emphasis on the different approaches to NPPV. Therefore, the aim of the current review article is to elaborate on the clinical and physiological reasons for why high-intensity NPPV is favourable to low-intensity NPPV.